High-performance deep red colloidal quantum well light-emitting diodes enabled by the understanding of charge dynamics - Hu, Sujuan (2022)
Colloidal quantum wells (CQWs) have emerged as a promising family of two-dimensional (2D) optoelectronic materials with outstanding properties, including ultranarrow luminescence emission, nearly unity quantum yield, and large extinction coefficient. However, the performance of CQWs-based light-emitting diodes (CQW-LEDs) is far from satisfactory, particularly for deep red emissions (≥660 nm). Herein, high efficiency, ultra-low-efficiency roll-off, high luminance, and extremely saturated deep red CQW-LEDs are reported. A key feature for the high performance is the understanding of charge dynamics achieved by introducing an efficient electron transport layer, ZnMgO, which enables balanced charge injection, reduced nonradiative channels, and smooth films. The CQW-LEDs based on (CdSe/CdS)@(CdS/CdZnS) ((core/crown)@(colloidal atomic layer deposition shell/hot injection shell)) show an external quantum efficiency of 9.89%, which is a record value for 2D nanocrystal LEDs with deep red emissions. The device also exhibits an ultra-low-efficiency roll-off and a high luminance of 3853 cd m-2. Additionally, an exceptional color purity with the CIE coordinates of (0.719, 0.278) is obtained, indicating that the color gamut covers 102% of the International Telecommunication Union Recommendation BT 2020 (Rec. 2020) standard in the CIE 1931 color space, which is the best for CQW-LEDs. Furthermore, an active-matrix CQW-LED pixel circuit is demonstrated. The findings imply that the understanding of charge dynamics not only enables high-performance CQW-LEDs and can be further applied to other kinds of nanocrystal LEDs but also is beneficial to the development of CQW-LEDs-based display technology and related integrated optoelectronics.